Multi‐instrument Observations of Mesoscale Enhancement of Subauroral Polarization Stream Associated With an Injection. Issue 3 (25th March 2019) - Wang, Zihan; Zou, Shasha; Shepherd, Simon G.; Liang, Jun; Gjerloev, Jesper W.; Ruohoniemi, J. Michael; Kunduri, Bharat; Wygant, John R.
Abstract: Subauroral polarization streams (SAPS) prefer geomagnetically disturbed conditions and strongly correlate with geomagnetic indexes. However, the temporal evolution of SAPS and its relationship with dynamic and structured ring current and particle injection are still not well understood. In this study, we performed detailed analysis of temporal evolution of SAPS during a moderate storm on 18 May 2013 using conjugate observations of SAPS from the Van Allen Probes (VAP) and the Super Dual Auroral Radar Network (SuperDARN). The large‐scale SAPS (LS‐SAPS) formed during the main phase of this storm and decayed due to the northward turning of the interplanetary magnetic field. A mesoscale (approximately several hundreds of kilometers zonally) enhancement of SAPS was observed by SuperDARN at 0456 UT. In the conjugate magnetosphere, a large SAPS electric field (∼8 mV/m) pointing radially outward, a local magnetic field dip, and a dispersionless ion injection were observed simultaneously by VAP‐A at L shell = 3.5 and M L T  = 20. The particle injection observed by VAP‐A is likely associated with the particle injection observed by the Geostationary Operational Environmental Satellite 15 near 20 MLT. Magnetic perturbations observed by the ground magnetometers and flow reversals observed by SuperDARN reveal that this mesoscale enhancement of SAPS developed near the Harang reversal and before the substorm onset. The observed complex signatures in both space and ground can be explained by a two‐loop current wedge generated by the perturbed plasma pressure gradient and the diamagnetic effect of the structured ring current following particle injection. Key Points: Mesoscale enhancement of SAPS was observed by VAP and SuperDARN on top of the existing large‐scale SAPS Mesoscale enhancement is associated with energetic ion flux increase, energetic electron flux decrease, and local magnetic field dip Mesoscale enhancement of SAPS and equatorward flow burst developed near the Harang reversal